2009
DOI: 10.1523/jneurosci.4648-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Filtering of Nociceptive Information by Dynamic Activation of Endogenous Pain Modulatory Systems

Abstract: Endogenous pain control mechanisms have long been known to produce analgesia during "flight or fight" situations and to contribute to cognitively driven pain modulation, such as placebo analgesia. Afferent nociceptive information can also directly activate supraspinal descending modulatory systems, suggesting that these mechanisms may participate in feedback loops that dynamically alter the processing of nociceptive information. The functional significance of these feedback loops, however, remains unclear. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 71 publications
9
130
0
Order By: Relevance
“…Functional magnetic resonance imaging studies have shown that several brain regions mediating pain relief are activated during induction of offset analgesia [74], and another study by Yelle et al [75] found increased activation of PAG, cerebellar regions, thalamus, dorsolateral prefrontal cortex, midcingulate cortex, and insular cortex.…”
Section: Offset Analgesiamentioning
confidence: 99%
“…Functional magnetic resonance imaging studies have shown that several brain regions mediating pain relief are activated during induction of offset analgesia [74], and another study by Yelle et al [75] found increased activation of PAG, cerebellar regions, thalamus, dorsolateral prefrontal cortex, midcingulate cortex, and insular cortex.…”
Section: Offset Analgesiamentioning
confidence: 99%
“…Functional imaging studies of CPM have identified reduced activity in several pain-processing areas including the thalamus, SI and SII as well as the anterior and middle cingulate cortex (ACC and MCC) and insula (INS) [28,30]. In contrast, OA reduces activity in SI, but produces greater activity in the periaqueductal gray (PAG), anterior INS, dorsalateral prefrontal cortex (DLPFC) and the MCC [7,42]. Since different noxious stimuli were applied across these different studies, it remains unclear if CPM and OA engage similar brain mechanisms of pain modulation.…”
Section: Introductionmentioning
confidence: 99%
“…There are well-known dynamic effects in pain that occur during continuous or fast repetitive noxious stimulation, such as temporal summation 13, 17, 24, 29, 33, 40, 41, 53 and offset analgesia (the disproportionately large decrease in thermal pain following a slight decrease in stimulus temperature) 19, 63, 64 . Temporal pain adaptation also occurs during sequences of more widely spaced noxious stimuli (e.g., separated by 10–80 seconds).…”
Section: Introductionmentioning
confidence: 99%